Badanie satysfakcji użytkowników WiMBP im. Cypriana Norwida w Zielonej Górze jako ważny element zarządzania jakością = User satisfaction surveys at the Cyprian Norwid Regional and City Public Library in Zielona Góra as an important element of quality management - Simonjetz, Monika; Domagała, Małgorzata (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
This article, which collates the results of user satisfaction surveys of the Cyprian Norwid Regional and City Public Library in Zielona Góra, addresses the issue of quality-of-service, understood as taking care of users and satisfying their needs and expectations. The main goal of the study was to obtain an opinion on the quality of the Library?s work. The concepts of quality-of-service and user satisfaction were defined on the basis of the analysis of scientific publications and articles in industry magazines and post-conference publications. The research was carried out from October 2016 to January 2017, according to the methodology of the nationwide project ?The Analysis of Functioning of Libraries? (AFL). 600 questionnaires were analyzed. The readers were diversified according to six age ranges: 13-15, 16-19, 20-24, 25-44, 45-60 and over 60 years. Respondents? answers were included in tabular summaries covering the following issues: frequency of visits to the library, purposes of visits, evaluation of all library services, evaluation of particular aspects of the functioning of the facility, evaluation of services in relation to the frequency of visits, and evaluation of individual services in relation to respondents? age. The research project carried out within the framework of the AFL project made it possible to determine the comparative user-satisfaction index of the Zielona Góra Regional Library, relative to other public, pedagogical and scholarly libraries. This is one of the most important functional indicators of library facilities, and is in line with international standards and recommendations, in particular: ISO 11620: 2008 Information and documentation ? Library performance indicators.
Keywords: biblioteka publiczna; Analiza Funkcjonowania Bibliotek; Satysfakcja użytkowników; Wskaźniki funkcjonalności bibliotek; public library; Analysis of Functioning of Libraries; User satisfaction; Library performance indicators